Dual-responsive nanoplatform for integrated cancer diagnosis and therapy: Unleashing the power of tumor microenvironment - Ma, Rui; Zhang, Peng; Chen, Xiuying; Zhang, Mengdi; Han, Qinghe; Yuan, Qinghai (Frontiers in Chemistry, 2024)
Chemodynamic therapy (CDT), designed to trigger a tumor-specific hydrogen peroxide (H2O2) reaction generating highly toxic hydroxyl radicals (·OH), has been investigated for cancer treatment. Unfortunately, the limited Fenton or Fenton-like reaction rate and the significant impact of excessive reducing glutathione (GSH) in the tumor microenvironment (TME) have severely compromised the effectiveness of CDT. To address this issue, we designed a dual-responsive nanoplatform utilizing a metal-polyphenol network (MPN) -coated multi-caged IrOx for efficient anti-tumor therapy in response to the acidic TME and intracellular excess of GSH, in which MPN composed of Fe3+ and tannic acid (TA). Initially, the acidic TME and intracellular excess of GSH lead to the degradation of the MPN shell, resulting in the release of Fe3+ and exposure of the IrOx core, facilitating the efficient dual-pathway CDT. Subsequently, the nanoplatform can mitigate the attenuation of CDT by consuming the excessive GSH within the tumor. Finally, the multi-caged structure of IrOx is advantageous for effectively implementing photothermal therapy (PTT) in coordination with CDT, further enhancing the therapeutic efficacy of tumors. Moreover, the outstanding Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) (T1/T2) multimodal imaging capabilities of IrOx@MPN enable early diagnosis and timely treatment. This work provides a typical example of the construction of a novel multifunctional platform for dual-responsive treatment of tumors.